EFFECT OF DEXAMETHASONE ON LIVER FUNCTION IN MALE RATS EXPOSED TO PARAQUAT - Rana A. Asim Man S. Kalo Soulaf J. Kakel (Basrah Journal of Veterinary Research)
study was conducted to evaluate the usage of dexamethasone (Dx) in the treatment of liver function tests in experimental paraquat (PQ)- induced oxidative stress in male albino rats. Three groups of rats were subjected to this trial, control, PQ group (50 mg/ kg orally) and PQ with Dx (50 mg/ kg orally, 4 mg/ kg ip. Respectively)daily throughout the 15 days. Results revealed that treatment with PQ caused a mortality rate in a ratio of 30%,significantly increased (p≤0.05) of glucose, cholesterol, bilirubin concentrations and alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and amylase activities but the concentrations of both triglycerides and serum proteins were reduced compared with control whereas the treatment of PQ- treated rats with Dx decreased mortality rate (30%) and corrected the activity of serum transaminases, alkaline phosphatase enzymes whereas Dx treatment induced an elevation in amylase activityin addition to the elevation of concentrations of total cholesterol, total protein and albumin in comparison with values of PQ- treated rats, Dx did not affect the concentration of glucose. In conclusion, the treatment of PQ- induced toxicity with Dx in rats was efficient in correction of most liver function tests.